Effects of metformin on the gut microbiota: A systematic review - Pavlo Petakh; Iryna Kamyshna; Aleksandr Kamyshnyi (Elsevier, 2023)
Background: The gut microbiota is increasingly recognized as a crucial factor in human health and disease. Metformin, a commonly prescribed medication for type 2 diabetes, has been studied for its potential impact on the gut microbiota in preclinical models. However, the effects of metformin on the gut microbiota in humans remain uncertain. Scope of review: We conducted a systematic review of clinical trials and observational studies to assess the existing knowledge on the impact of metformin on the gut microbiota in humans. The review focused on changes in bacterial composition and diversity following metformin treatment. Major conclusions: Thirteen studies were included in the analysis. The results revealed alterations in the abundance of bacterial genera from various phyla, suggesting that metformin may selectively influence certain groups of bacteria in the gut microbiota. However, the effects on gut microbiota diversity were inconsistent across populations, with conflicting findings on changes in alpha and beta diversity measures.Overall, the use of metformin was associated with changes in the abundance of specific bacterial genera within the gut microbiota of human populations. However, the effects on gut microbiota diversity were not consistent, highlighting the need for further research to understand the underlying mechanisms and clinical significance of these changes.